VD_FINDINFO Décision / 2012 / 194 vom 9. Dezember 2011 - VD Tribunal cantonal (2011)
DÉTENTION PRÉVENTIVE, RISQUE DE COLLUSION, RISQUE DE FUITE, PROPORTIONNALITÉ | 221 al. 1 let. a CPP (CH), 221 al. 1 let. b CPP (CH), 222 CPP (CH), 227 CPP (CH), 393 al. 1 let. c CPP (CH)